Doing Sex Work in Manila: Bodies and Selves - Abaya, Eufracio C. (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
Using data derived from field work and published literature, this paper examines how some female sex workers in two cities in Metro Manila live their lives in a constraint-ridden social world. Analysis shows that sex workers have developed strategies and tactics to confront such pressures as social prejudices, local morality, family obligations, risks in sex work and health imperatives. The paper also calls attention to some areas to consider in designing sexual and reproductive health interventions for female sex workers.